Prawo cudzoziemców do samorządu lokalnego Ukrainy w warunkach eurointegracji - Radiševs'ka, Olesâ Rostislavívna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The article aims to present the influence of EU law on changes to Ukrainian law as a way to bolster Ukraine’s progress towards European integration. The author analyzes the legal basis for determining the composition of the so-called territorial community, as well as the views and approaches to the possibility of recognizing foreign members of local communities in Ukraine. Ukraine has to harmonize national legislation with European standards in the area of local democracy (local government). The principle of equality between citizens of one Member State and citizens of other Member States of the EU is regarded as the basic principle of EU law
Keywords: Ukraina; samorząd lokalny; obywatel; cudzoziemcy; mieszkaniec; prawa wyborcze; służba publiczna; zasada równości